MENINGKATKAN MINAT DAN HASIL BELAJAR KOMPUTER AKUNTANSI MELALUI PENERAPAN METODE PROBLEM BASED LEARNING PADA SISWA KELAS XII-AKL 2 SMK NEGERI 1 PAMEKASAN - Irwan Jaya (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2022)
This study aims to determine changes in class XII-AK 2 students' interest and learning achievement in Computer Accounting subjects using the problem-based learning method, as well as changes in class XII-AKL2 students' learning outcomes in Computer Accounting subjects at SMK Negeri 1 Pamekasan. This study consists of two cycles of classroom action research: cycle I and cycle II. This study's sample consisted of 25 students from class XII-AKL 2-SMK Negeri 1 Pamekasan. Data collection techniques used are written tests, questionnaires, observation. In data analysis, descriptive analysis was used. Data analysis revealed that students' learning skills improved from cycle I to cycle II, with cycle I having an average score of 68.4 and a percentage of less than 44 percent (11 students), sufficient 24 percent (6 students), and good 32 percent (32 students) (8 students). In cycle II, the average score is 79.6, with less than eight percent (2 students), sufficient twelve percent (3 students), and good activity eighty percent (20 students). After the teaching and learning process with the application PBL Learning Method, student achievement results also demonstrate changes. Thus, the level of cycle II student learning completion has been formally declared complete. The conclusion of this study is that problem-based learning learning methods can have a positive effect on students in the learning process, particularly in terms of improving student achievement, as indicated by the increase in the average score of students from 67.2 with learning completeness reaching 56% in the first cycle to 80.4 with learning mastery reaching 92% in the second cycle.